Commentary: A Reassessment of the Taxonomic Position of Mesosaurs, and a Surprising Phylogeny of Early Amniotes - MacDougall, Mark J.; Modesto, Sean P.; Brocklehurst, Neil; Verrière, Antoine; Reisz, Robert R.; Fröbisch, Jörg (Frontiers in Earth Science, 2018)
The early amniote clade Mesosauridae has long been of interest to scientists, primarily due to the members of the clade being the oldest secondarily aquatic tetrapods and their role as a line of evidence for continental drift. In the landmark phylogenetic analysis of Parareptilia by Gauthier and colleagues in 1988, Mesosauridae was found to be the sister taxon of all included parareptiles. Over the last three decades several studies regarding the phylogenetic placement of mesosaurs have helped to reinforce their position as the most basal parareptile clade. The most recent study of Mesosauridae is by Laurin and Piñeiro, who reassess the phylogenetic position of the clade within early amniotes. This new analysis recovered mesosaurs as being the sister clade to all other sauropsids, supporting the results of an earlier study by Laurin and Reisz in 1995. However, we feel that there are two main issues with this new study that need to be addressed. The first is the use of an outdated phylogenetic matrix and the fact that the authors patently ignore over two decades of parareptilian research when conducting their phylogenetic analysis, whereas the second involves the problems associated with lateral temporal fenestration and its extreme variability in reptiles. We discuss how these two issues could have influenced the results that were obtained from this study, and how, when they are taken into account, a different picture regarding the phylogenetic position of Mesosauridae is reconstructed to that of Laurin and Piñeiro.